Peran Subsektor Peternakan dalam Perekonomian Jawa Timur - Abdirahman, Fauzi; Tide, Versi Vergian; Amalina, Khairina Nur; Nadvira, Teiza; Firman, Achmad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
East Java Province is a region with a high Gross Regional Domestic Product (GRDP) in the livestock sector. Therefore, this sub-sector is one of the main core businesses of East Java Province. The purpose of the study was to analyze the development of livestock production rates, economic growth, absorption of the number of workers, and investment development in the livestock sub-sector of East Java Province. The research method used quantitative research using basic statistical analysis tools. The results of the study showed that the trend of the rate of development of livestock production increased in beef poultry and milk commodities, while in egg commodities it decreased. The trend of economic growth based on GRDP at Current Prices (ADHB) has increased. The trend of labor absorption has increased from 2018 to 2022. The trend of investment development in the livestock sub-sector based on Domestic Investment (PMDN) has increased, while Foreign Investment (PMA) has decreased.